2018
DOI: 10.1111/jog.13820
|View full text |Cite
|
Sign up to set email alerts
|

Human omental adipose‐derived stem cells from donors with different body mass index had similar effects on proliferation and migration of endometrial cancer cells in vitro

Abstract: Aim: This study aimed to confirm whether human omental adipose-derived stem cells (O-ASC) from donors with varying body mass index (BMI, calculated in kg/m 2 ) exert different effects on proliferation and migration of endometrial cancer (EC) cells. Methods: Omental adipose-derived stem cells were isolated from the omental adipose tissues of eight patients who were diagnosed with EC aged from 35 to 56 years. According to the patients' BMI, the O-ASC was divided into two groups: obesity group (BMI ≥ 30) and norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…De Girolamo et al reported lower expression of CD54 and CD34 in obASCs than in lnASCs [ 17 ]. On the other hand, it has been reported that obesity of the donor does not affect the CD marker expression of ASCs [ 26 , 44 , 45 ]. In the current study, ASC from all donors showed a characteristic immunophenotype of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…De Girolamo et al reported lower expression of CD54 and CD34 in obASCs than in lnASCs [ 17 ]. On the other hand, it has been reported that obesity of the donor does not affect the CD marker expression of ASCs [ 26 , 44 , 45 ]. In the current study, ASC from all donors showed a characteristic immunophenotype of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Direct co-cultured experiments found that O-AT-MSC could fuse with endometrial cancer Ishikawa and HEC-1-A cells to spontaneously form hybrid tumor spheres, leading to the enhanced cancer mobility and heterogeneity. According to body mass index (BMI), Li et al [ 101 ] further obtained the O-AT-MSC from endometrial cancer patients with different BMI (BMI ≥ 30 and 18.5 < BMI < 24.9). Although the promotive effects of the O-AT-MSC on the proliferation and migration of HEC-1-A and Ishikawa cells were comparable, no significant differences were observed between the two groups.…”
Section: Challenges Of Msc-based Strategies In Gynecologic Cancer The...mentioning
confidence: 99%
“…However, the regulatory mechanisms involving CFTR in EC may be opposite in vitro compared to the in vivo conditions. Additionally, in Ishikawa cells, blockade of volume-activated chloride channels (VACC) with 5-nitro-2-(3-phenylpropyl-amino)-benzoate (NPPB) inhibited invasion and regulatory volume decrease in a dose-dependent manner [92]. Voltage-dependent anion channel-1 (VDAC1) and VDAC3 are overexpressed in EC in comparison to normal tissues, and higher expression of all VDAC or protein expression of VDAC2 was associated with poor prognosis [93].…”
Section: Endometrial Cancermentioning
confidence: 99%